The Contrast Between The Pronouns Of The Speaker And The Addressee Attached And Detached Pronouns In The Surahs Of Al-Hawameem As A Model/ المناسبة في تقابل ضمائر المتكلم المخاطب الضمير المتصل والمنفصل في سور الحواميم أنموذجاً - Fatima Ismail Obaid Dahi Al-Mohannadi; Bayan Shakir Jumah Bakri Al-Kubaysi (Ijaz Arabi Journal of Arabic Learning, 2026)
This study examines the use of attached and detached pronouns in the Qur'anic discourse, highlighting their role in shaping meaning and guiding the message. Through various Qur’anic examples. the research shows how pronouns structure the dialogue between God, the Prophet, and the people, enhancing textual cohesion and rhetorical impact. It concludes that pronouns serve theological and communicative functions, representing a key feature of the Quran